Designing Khit Silk Scarves by the Khit Silk Weaving Community Enterprise Groupin Udon Thani Province - Wongarree, Pakasid; Phongsai, Sucheera (Journal of Cultural Approach, 2025)
This research aimed to 1) study the utilization of colors and patterns in Khit silk scarves, 2) study designing the Khit silk scarves, and 3) study consumer satisfaction with the design of Khit silk scarves produced by the Khit silk weaving community enterprise group in Udon Thani province. Researchers selected five experts in silk weaving and pattern design, along with 30 members of the Khit silk weaving group in Nong Oa village, Nong Wua Soh District, Udon Thani Province, as samples. Research tools used included expert opinion questionnaires and satisfaction questionnaires, with statistical analysis including frequency, percentage, means, and standard deviation. The findings of this study revealed that 1) the use of colors and patterns, specifically the utilization of colors, consisted of 11 natural dyes, i.e., indigo blue from the indigo tree, red from lac, green from sappan leaves, pink from sappan wood, dark yellow from cockspur thorn core, black from ebony fruit, gold from red lotus, silver from red lotus stalks, brown from golden shower pods, and soft yellow from pomegranate. The art pattern design consisted of nine patterns: Kapu Um Dao pattern, Maeng Ngod pattern, large swan pattern, Pan Maha pattern, Mak Nut pattern, Baisri Um Dao pattern, Kab Um Dao pattern, Dao Chom pattern, and Ngoan Nguak pattern. 2) Designing Khit silk scarves was performed three ways, including Khit silk scarves with Khaw Lohng pattern, Ta Phao Lohng Kao pattern, and Pikul pattern. Specialists chose type I of the Khaw Lohng pattern, type II of the Ta Phao Lohng Kao pattern, and type I of the Pikul pattern. 3) Consumer satisfaction with the design of Khit silk scarves at Baan Nong Oa, Nong Wua Soh District, Udon Thani Province, included three aspects: color and pattern satisfaction with the highest level of 4.67; design satisfaction with the highest level of 4.85; and product satisfaction with 4.82, respectively.